2015
DOI: 10.1038/pr.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neutrophil gelatinase-associated lipocalin predicts acute pyelonephritis in children with urinary tract infections

Abstract: Background:The identification of acute pyelonephritis (APN) is still a challenge. Methods: Patients admitted for their first urinary tract infection (UTI) were enrolled. Plasma neutrophil gelatinaseassociated lipocalin (NGAL) levels were measured at admittance and after treatment. Laboratory, clinical, and imaging results were compared between children with and without APN. results: A total of 123 patients were enrolled (53 APN and 70 lower UTI). After adjusting for age and gender, plasma NGAL levels were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…While a study in adults found that uNGAL did not differentiate upper and lower tract infection, despite a significant difference in uNGAL between patients with UTI and controls, a pediatric study did report a difference in pNGAL levels between lower tract UTI and pyelonephritis [24, 25]. These results are consistent with the utility of pNGAL as a marker of inflammation and bacterial infection, while uNGAL is specific for localized infection with the genitourinary system.…”
Section: Ngal and Pyelonephritismentioning
confidence: 67%
“…While a study in adults found that uNGAL did not differentiate upper and lower tract infection, despite a significant difference in uNGAL between patients with UTI and controls, a pediatric study did report a difference in pNGAL levels between lower tract UTI and pyelonephritis [24, 25]. These results are consistent with the utility of pNGAL as a marker of inflammation and bacterial infection, while uNGAL is specific for localized infection with the genitourinary system.…”
Section: Ngal and Pyelonephritismentioning
confidence: 67%
“…Evolving biomarkers have been studied for non-invasive detection of APN in children with UTI [ 8 9 10 11 ]. Although several studies have revealed promising results for neutrophil gelatinase-associated lipocalin (NGAL) in children with UTI [ 9 10 11 ], only limited data are available for infants [ 12 13 ]. This study aimed to assess whether plasma NGAL (pNGAL) could be used as a reliable marker for renal parenchymal involvement and to determine the appropriate diagnostic cut-off value of NGAL for detection of renal parenchymal involvement in infants with febrile UTI.…”
Section: Introductionmentioning
confidence: 99%
“…We excluded patients with abnormal kidney function tests from the study group so that the NGAL values were not affected by any kidney pathology. In a study conducted by Sim et al (13) serum NGAL values in children who had UTI and developed pyelonephritis as a result were significantly higher than those with UTI but did not develop pyelonephritis, and the reason for that difference was the development of proximal tubular damage in the kidneys. However, this condition is not sufficient to explain the fact that controls' NGAL values were higher than the NGAL values of patients with UTI.…”
Section: Discussionmentioning
confidence: 94%